Irreducible Aspects of Embodiment: Situating Scientist and Subject. Issue 2 (3rd April 2018) - Brancazio, Nick
Abstract: Feminist philosophers of science have long discussed the importance of taking situatedness into account in scientific practices to avoid erasing important aspects of lived experience. Through the example of Gillian Einstein's [2012 ] situated neuroscience, I will add support to Gallagher's [2019 ] claims that intertheoretic reduction is problematic and provide reason to think pluralistic methodologies are explanatorily and ethically preferable.